The Relationship Between Some Physical Measurements and Flexibility of Handball Goalkeepers - Mohammed Hussein, M.M. Mustafa (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This study aims to examine the relationship between selected physical measurements and the flexibility of handball goalkeepers, as flexibility plays a crucial role in improving reaction speed, agility, and overall performance in defending the goal. A descriptive correlational method was applied, involving [insert number] male handball goalkeepers from [insert location/club/university if available]. Anthropometric measurements such as height, weight, arm span, and leg length were taken, along with standardized flexibility tests. Data were analyzed using Pearson’s correlation to identify associations between physical characteristics and flexibility levels. The results indicated that certain physical measurements, particularly arm span and leg length, showed a significant positive correlation with flexibility, while body weight demonstrated a negative relationship. Height was found to have a moderate influence but not statistically significant. Overall, the findings suggest that body proportions, especially limb length, contribute substantially to flexibility and performance effectiveness in goalkeeping. In conclusion, physical measurements play an important role in determining flexibility levels among handball goalkeepers. Coaches and trainers are encouraged to consider anthropometric profiles during athlete selection and training design, alongside flexibility-enhancing exercises, to maximize goalkeeper performance.